2018
DOI: 10.4235/agmr.2018.22.3.130
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Heart Proportions Compressed by Chest Compressions Between Geriatric and Nongeriatric Patients Using Mathematical Methods and Chest Computed Tomography: A Retrospective Study

Abstract: Background Current guidelines recommended that chest compression depths during car-diopulmonary resuscitation (CPR) should be at least one-fifth of the external chest ante-riorposterior (AP) diameter. The chest AP diameter increases because of dorsal kyphosis, senile emphysema, and poor lung compliance associated with aging. This study aimed to compare the proportion of the heart compressed by chest compression (based on the ejection fraction [EF]) in geriatric and nongeriatric patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
3
4
1
Order By: Relevance
“…Our results indicated that lower HCF was found among higher BMI groups which were consistent with the previous findings [15,19,21]. This might be explained by obese patients having a wider thoracic compartment and larger non-cardiac soft tissue, whereas CC depth was fixed at 50 mm to 60 mm.…”
Section: Plos Onesupporting
confidence: 92%
See 3 more Smart Citations
“…Our results indicated that lower HCF was found among higher BMI groups which were consistent with the previous findings [15,19,21]. This might be explained by obese patients having a wider thoracic compartment and larger non-cardiac soft tissue, whereas CC depth was fixed at 50 mm to 60 mm.…”
Section: Plos Onesupporting
confidence: 92%
“…Based on the cardiac pump model, direct CC mainly generated approximately 33% of the ejection fraction in normal adults, i.e., EF of 67% in 70 kilograms of healthy people [6,7]. The results of mean HCF from 38.3% to 50% were estimated by 50 mm and 60 mm CC depth and were consistent with other findings in Asia, which ranged from 37.1% to 54.6% [15,19,21]. Therefore, 50 mm to 60 mm CC depths might generate sufficient cardiac output during CPR.…”
Section: Plos Onesupporting
confidence: 84%
See 2 more Smart Citations
“…The use of computed tomography (CT) to calculate the heart compression fraction (HCF), which represents the blood flow generated during CPR, has been suggested for comparison of the appropriate CC depth 7 , 8 , 9 . Previous recommendations of a 50- and 60-mm CC depth were generalized and not categorized by factors such as sex, BMI, or specific diseases of the thoracic cage.…”
Section: Introductionmentioning
confidence: 99%